Higher education policy : an international comparative perspective - Goedegebuure, L. C. J. (Issues in higher education (Oxford, England), 1993)
Tremendous changes are affecting the structure and funding of higher education in many countries. This volume attempts to identify and analyze the principles, structural features and modes of work of the different higher education policies operating in eleven countries, as well as their commonalities and differences in the light of both general international trends and country-specific factors.